ANALISIS FAKTOR-FAKTOR PENGHAMBAT INVESTASI DI TIGA SEKTOR EKONOMI UTAMA PROVINSI LAMPUNG - Ismono, R. Hanung (Indonesian Journal of Socio Economics)
Research aim to identify and analyse factors pursuing invesment in agricultural sector, commercial sector, restaurant and hotel, and also processing industrial sector. Research method the usedÂ  partisipative method with interview in-depth, observations, and focused group discussions.Â  Study locationâs are Kota Bandar Lampung, Kabupaten Lampung Selatan, Kabupaten Lampung Tengah, dan Kabupaten Lampung Utara.Â  Research respodent is entrepreneur in especial sector agricultural sector, commercial sector, restaurant and hotel, and also processing industrial sector.Â  Amount of responder in this research are 100 entrepreneurâs.Â  Research analysis that used are descriptive statistic, frequency statistic, and tabulation data. Result of research indicate that factors resistor of invesment in Lampung Province are rule of law and security, conflict of land (agrarian), quality of policy support and infrastructure, licensing procedure to launch out, human investment, poblems of labour, banking intermediation to corporate world not yet is optimal, financial support for agriculture sector and UKM, and banking as safety player: banking not yet focused to real sector sector.